Navigational aid system with dynamic tide - Mahmud, Mohd. Razali; Tengku Ali, Tengku Afrizal (2005)
Nowadays, maritime transportation becomes one of the most important to the trade and industry of many countries. In any transportation, safety must be the main concern. As seawater is dynamic, the navigation happens to be difficult without any equipment or guidance such as Global Positioning System (GPS) and Electronic Chart Display and Information System (ECDIS). ECDIS are rapidly gaining popular acceptance as powerful for increasing navigational safety and augmenting situational awareness. However, most of the ECDIS do not represents the actual depth of water. It is the goal of this study to develop a system that will be able to update the water depth depending on tidal levels at given date and time, with various size of vessels draft and determines locations of the sea that is safe for vessels to sail through. Although there are several factors that should be taken into account to ensure adequate under keel clearance, this study only take the draft of the vessel as a main factor. Other factors that may cause the changes in under keel clearance are excluded. This system was developed using Microsoft Visual Basic 6.0 and Map Objects 2.0 to visualize the spatial data and with tidal data prediction in Microsoft Access database. Therefore, users without Geographic Information System (GIS) exposure can easily use this system. Mapping technique in GIS added an excellent visualizing, which can provide information in decision-making in order to know the right passage without jeopardize the vessels. The result of this system is the map location of the sea that has sufficient depth levels for vessels with different sizes to sail through. Safe depths are marked as blue points and locations without safe depths are marked with red points. For planning purposes, calculation of tide can be made and this will produce a graph showing the times of sufficient tide in blue and times of insufficient tide in red. The benefit of this system would be an improvement in port safety because the actual depth of water and safely navigable area for a vessel of particular draft is displayed on the system in real time.